ESTABLISHING A VIRTUAL FEEDBACK WITH STUDENTS DURING THE LECTURE - Zeinullayeva, И.Д; Kerimbayev, Н.Н; Beissov, Н.К; Azybaev, М (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
Since the main form of teaching in higher education is a lecture, the main didactic goal of the lecture is to form the necessary basis for teaching students teaching materials. The most vulnerable aspect of traditional education is the students' indifference to the one-sided high activity of the teacher. For this reason, the number of lecture types has recently increased. Lectures using feedback methods are one way to energize students. One of the ways to effectively use information technology is to provide virtual feedback to students during lectures. In this work, an experiment was carried out using a virtual feedback tool. The importance of virtual feedback is emphasized and practical examples are given